2023
DOI: 10.1186/s40168-023-01560-8
|View full text |Cite
|
Sign up to set email alerts
|

Synthase-selected sorting approach identifies a beta-lactone synthase in a nudibranch symbiotic bacterium

Abstract: Background Nudibranchs comprise a group of > 6000 marine soft-bodied mollusk species known to use secondary metabolites (natural products) for chemical defense. The full diversity of these metabolites and whether symbiotic microbes are responsible for their synthesis remains unexplored. Another issue in searching for undiscovered natural products is that computational analysis of genomes of uncultured microbes can result in detection of novel biosynthetic gene clusters; however, their in viv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 117 publications
0
0
0
Order By: Relevance
“…However, screening programs show that if secondary metabolites are explored using approaches already in use and using easily accessible samples, such as plants, compounds are often rediscovered. In recent years, therefore, research efforts have focused on little-explored sources, such as the microbiomes of marine animals [75].…”
Section: Biological /Pharmacological Activities Of Secondary Metaboli...mentioning
confidence: 99%
“…However, screening programs show that if secondary metabolites are explored using approaches already in use and using easily accessible samples, such as plants, compounds are often rediscovered. In recent years, therefore, research efforts have focused on little-explored sources, such as the microbiomes of marine animals [75].…”
Section: Biological /Pharmacological Activities Of Secondary Metaboli...mentioning
confidence: 99%
“…coli fatty acid biosynthesis and identify novel CPs from a tunicate microbiome using targeted single-cell genomics . Furthermore, we and others have exploited the environmental sensitivity of fluorophores like DMN to visualize protein–protein interactions in CP-dependent fatty acid biosynthesis. While these studies have demonstrated the efficacy of fluorescent CP-targeting probes as chemical tools, weak intensity and low signal-to-noise ratio dampened an otherwise robust ability to manifest specific bioactivity. The work described herein was designed with the goal of improving certain aspects of solvatochromic pantetheinamides by exploring dyes which change color in addition to improved fluorescence intensity to report on their local microenvironment.…”
Section: Introductionmentioning
confidence: 99%